(untitled) (The International Journal for Scientific Research, 2026)
This study aims to measure the level of institutional wellbeing among employees of the Commission for Statistics and GIS in Iraq using the Positive Statistics methodology through the application of the PERMA model derived from positive psychology. The study adopts a descriptive analytical approach to examine the relationship between the dimensions of wellbeing and employees’ perceptions of their work environment. Data were collected using a questionnaire consisting of 26 items distributed across five dimensions: positive emotion, engagement, relationships, meaning, and accomplishment. The study sample consisted of 114 employees working in different departments of the organization. The reliability of the measurement instrument was tested using Cronbach’s Alpha, which reached 0.951, indicating a high level of internal consistency among the questionnaire items. Descriptive statistical analysis showed that the overall mean of institutional wellbeing reached 4.02 on the five-point Likert scale, reflecting a relatively high level of wellbeing among employees in the institution. Within the framework of Positive Statistics methodology, the Positive Empowerment Index (PEI) was calculated for the five PERMA dimensions to standardize the interpretation of wellbeing indicators. The results revealed that PEI values ranged between 0.68 and 0.81, indicating generally high levels of positive empowerment across the examined dimensions. Multiple regression analysis showed that the PERMA dimensions collectively explain 56.3% of the variance in satisfaction with the work environment (R² = 0.563). The accomplishment dimension emerged as the most influential factor affecting institutional satisfaction (Beta = 0.533, Sig = 0.000). The findings highlight the importance of professional accomplishment and positive emotional experiences in strengthening institutional wellbeing and demonstrate the value of the Positive Statistics methodology as an analytical approach for measuring empowerment and improvement factors within organizations.